THE 40AR/39AR DATING OF MAGMATIC ACTIVITY IN THE DONBAS FOLD BELT AND THE SCYTHIAN PLATFORM (EASTERN EUROPEAN CRATON) - Alexandre P.; Chalot-Prat F.; Saintot A.; Wijbrans J.; Stephenson R.; Wilson M.; Kitchka A.; Stovba S. (My University, 2004)
The Donbas Fold Belt is the compressionally deformed southeasternmost part of the intracratonic late Paleozoic Dniepr-Donets rift basin. It is situated in an intracratonic setting but close to the southern margin of the East European Craton, south of which lies the Scythian Platform. A range of igneous rocks from the Donbas Fold Belt and the Scythian Platform were dated by the 40Ar/39Ar method in order to constrain the ages of magmatic activity in these areas, and compare them. The plateau ages from the south margin of the Donbas Fold Belt vary from 151.4 ± 4.7 Ma to 278.1 ± 5.3 Ma, and define three main age groups: Middle-Late Jurassic, Middle-Late Triassic, and Early Permian. The age spectra obtained from the Scythian Platform samples are often disturbed as a result of limited alteration. The proposed ages (plateau and pseudoplateau) vary from 174.4 ± 2.1 Ma to 243.7 ± 1.4 Ma, and two major age groups are defined, in Early Carboniferous and Triassic/Jurassic times. The Early Permian (285–270 Ma) and Early Triassic (245–250 Ma) ages of magmatic activity are the same in both areas; in the Late Triassic, the ages of magmatic activity are slightly different (220 and 205 Ma), and they are entirely different thereafter. These data can be interpreted as indicating a mantle plume as common deep magmatic source.
Keywords: geochronology; 40Ar/39Ar; Donbas Fold Belt; Scythian Platform; magmatic activity; mantle plume; Mesozoic::Jurassic; Mesozoic::Triassic; Мезозой::Триасовая; Палеозой::Пермская; Мезозой::Юрская; Paleozoic::Permian